Pengujian Black Box pada Aplikasi Sistem Pengarsipan Surat Menggunakan Teknik Equivalence Partitions - Handy Nur; Ihda Setiaji Nugroho; Muhammad Rizki Eka Saputra; Nanang Suhaemi; Aries Saifudin (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
Archiving is usually carried out by the secretary or administration. The archive manager usually does it manually, it makes the number of archives stored and looks increasingly unorganized on the filing shelf. As a result, the archiving section will need a lot of time to search for documents that have long been stored. Especially in the modern era, the development of increasingly sophisticated technology will help the archiving in managing the records in the room or office. One of them is through software testing or software testing, this device is one of the software tools used to obtain information or results on the quality of a product and service application. This test in addition to looking for errors or defects of an application also has other functions, such as testing how far the capabilities of the application or system. Equivalence Partitions Technique is a test based on entering data in 2 (two) forms in a letter archive application, each menu input will be tested and grouped according to function whether it is true or false. So expect the quality of the software produced in accordance with the expected function.